1999
DOI: 10.1080/18811248.1999.9726234
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Wear Marks on Fast Reactor Fuel Pin Cladding

Abstract: The surfaces of fuel pin cladding and spacer wire wound round it in the JOYO Mark-I and EBR-II test fuel were found to carry wear marks. Out-of-pile experiments indicated that simple hydraulic vibration could not constitute the cause of marking. Assuming the alternative factor of thermohydraulic vibration to be the cause, a model has been devised, applying which a method is proposed for estimating the ranges in which wear and contact marks can respectively be expected to occur. The two ranges are determined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In the literature [57], a need to research fretting for MYRRHA has been identified, but fatigue on the other hand is not expected [57,58]. Wear marks due to contact have been observed in real reactors with wire-wrapped fuel assemblies in hexagonal array [59]. The contact forces obtained from the simulations of present work can be used to calculate an estimate of the expected wear rate due to FIV, in order to meet this demand for fretting analysis.…”
Section: Introductionmentioning
confidence: 89%
“…In the literature [57], a need to research fretting for MYRRHA has been identified, but fatigue on the other hand is not expected [57,58]. Wear marks due to contact have been observed in real reactors with wire-wrapped fuel assemblies in hexagonal array [59]. The contact forces obtained from the simulations of present work can be used to calculate an estimate of the expected wear rate due to FIV, in order to meet this demand for fretting analysis.…”
Section: Introductionmentioning
confidence: 89%
“…To obtain a small water volume fraction in core, tight lattices are necessary. Wire wrap spacers, an alternative to grid spacers, have been used extensively in LMFBR [3] and tight-lattice high-conversion cores [4], mainly due to their advantageous pressure drop and better mixing capability. As a consequence, the required coolant pumping power is decreased and the coolant temperature profile inside the fuel bundle is flattened which will obviously decrease the peak cladding temperature.…”
Section: Introductionmentioning
confidence: 99%